Innovative Superhard Materials and Sustainable Coatings for Advanced Manufacturing Proceedings of the NATO Advanced Research Workshop on Innovative Superhard Materials and Sustainable Coatings Kiev, Ukraine 12-15 May 2004 - Lee, Jay.; Novikov, Nikolay; Turkevich, Vladimir; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The book contains the results of the latest achievements of leading researchers from 9 countries in the field of diamond and diamond-like carbon, cubic boron nitride and other superhard materials; high-density engineering ceramics; high pressure-high temperature technique; computer-aided modeling; diamond, cubic boron nitride, ceramic and cemented carbide tools; development, production and applications of nanostructured materials; films and wear-resistant coating; methods for quality control of tool materials and tools.
The Bridge Between the Ideal and Real Mechanical Properties for Superhard Materials -- Thermodynamic and Kinetic Aspects of Spontaneus Crystallization of Diamond and Cubic Boron Nitride -- Strain-Induced Disorder and Phase Transformation in Hexagonal Boron Nitride under Quasi-Homogeneous Pressure up to 25 GPa: In-Situ X-Ray Study in a Rotational Diamond Anvil Cell -- Combining Hard with Soft Materials in Nanoscale under High-Pressure High-Temperature Conditions -- Advanced Manufacturing of Advanced Materials -- High-Pressure Synthesis of MgB2-Based Material with High Critical Currents -- Promising Superhard Materials and Efficient Technologies of Their Production -- Light Element Polycrystalline Structures Incorporating Micron to Nanosize Constituents -- Electrical Properties of Crystalline 3D-Polymeric C60 Fullerites Obtained by HPHT Treatment -- The Influence of Detonation Nanodiamond Powder on Blood Cells -- Structural and Adsorption Characteristics of Porous Industrial Diamond -- Influence of Initial Diamond Raw Material Strength on Quality of Produced on Its Base Thin Micron Powders -- Recent Progress in Growth of Diamond Crystals -- Peculiarities of Graphite Transformation under High Pressure -- Thin Film Coatings as a Sensor Fabricated on Mechanical Parts -- Grain Boundary Engineering of Nanostructured Chromium Films -- Phosphorus Related Characteristics of Synthetic Diamonds -- A Survey of Coating Technologies in Japanese Small and Medium Enterprises -- Tribological Properties of ta-C Films Deposited on Hard Metal Substrate -- Application of Diamond-Like Carbon Film in Optical Waveguide Sensing System -- Recent News of Manufacture of Hip Joint Prostheses: Problems and Solutions -- Capillary Phenomena, Phase Interaction at the Graphite-Metal Melt Interface and Diamond Synthesis -- Mechanism of Cubic Boron Nitride Formation and Phase Equilibria in the Mg-BN and AlN-BN Systems -- Amorphous Diamond, Its Production, Identification and Some Properties -- The Effect of the Field of Residual Strains on the n-Beam X-Ray Diffraction on Diamond -- Phase Diagram and Diamond Synthesis in the Aluminum-Carbon System at a Pressure of 8 GPa -- Superconducting Tunnel Junctions with Inelastic Processes in Barriers -- Diamond-Carbon Composites. Physico-Chemical Properties, New Areas of Their Application -- Chemical Properties of Nanodiamond -- Surface Chemistry of Submicron cBN Powders -- Uniformity of Superhard Material Grinding Powders -- The Influence of Conditions of the Detonation Synthesis (DS) on the Degree of Transformation and Physico-Chemical Properties of Detonation Diamonds (DD) -- The Effect of the Structure of a Two-Layer Cutting Insert on Its Physicomechanical Characteristics -- Comparative Study of Near Stochiometric a-SiC:H and a-SiC Films: Effect of the Bonded Hydrogen -- Certification of Hardened Diamond Like Coatings (DLCs) Mechanical Properties -- The Modification of Tribological Properties of Diamond Like Coatings (DLCs) Obtained by Graphite Sputtering in Argon and Nitrogen Ions Presence -- Application of Diamond-like Films for Improving Transparency in the IR -- Influence of the Temperature on Electronic Properties of Carbon-Rich BN Films Obtained from (C2H5)3B by Means of Reactive Pulse Plasma Method -- New Technological and Hardware Resources of Creation Multilayered Protective Functional Coatings -- Effect of Corrosion Environment on the Fatigue Behavior of WC - Co Hard Alloy Teeth of Drill Bits.
Keywords: CHEMISTRY; CHEMISTRY, PHYSICAL ORGANIC; CONDENSED MATTER; STRUCTURAL CONTROL (ENGINEERING).; CHEMISTRY, INORGANIC; CHEMISTRY; TRIBOLOGY, CORROSION AND COATINGS; CONDENSED MATTER; OPERATING PROCEDURES, MATERIALS TREATMENT; PHYSICAL CHEMISTRY; PHYSICS AND APPLIED PHYSICS IN ENGINEERING; MATERIALS SCIENCE